Galangin reduces MPTP-induced dopamine neuron injury via the autophagy dependent-PI3K/AKT pathway - Huang, Liping; Li, Qiaofeng; Wu, Jingyi; He, Yingying; Huang, Junwei; Xie, Sipeng; Yang, Canfeng; Ruan, Qingling; Zhou, Zhongliu; Deng, Minzhen (Frontiers in Aging Neuroscience, 2025)
IntroductionResearch has confirmed that Galangin can attenuate autophagy and protect dopaminergic neurons. This study aims to clarify whether Galangin attenuates dopaminergic neuron injury by regulating the PI3K/AKT pathway in Parkinson’s disease (PD) model mice.MethodsThe study explores the mitigating effects of Galangin on PD processes by administering 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) to induce the condition. Techniques including network analysis, transcriptomic analysis, rotarod test, enzyme-linked immunosorbent assay (ELISA), qRT-PCR, western blotting, immunohistochemistry, immunofluorescence, and hematoxylin–eosin (HE) were employed to unveil the molecular changes induced by Galangin.ResultsThe network pharmacological analysis showed 301 targets related to Galangin, and 2,858 genes related to PD. Galangin treatment can improve the motor coordination of PD model mice, reduce damage to neurons in the brain, improve the antioxidant capacity and reduce the inflammatory damage of brain tissue. Additionally, Galangin suppressed mRNA expression of PD markers (IL-1β, TNF-α, IL-6, SRC and PTGS2), elevated protein levels of GSH-Px, SOD, P-PI3K, P-CREB, P-AKT, TH, BDNF and P62, while decreasing α-syn, SRC, MDA, Beclin-1 and LC3B expression. Moreover, the expression of significantly different genes in the Galangin-treated group and model group analyzed by transcriptomics was basically consistent with the qRT-PCR verification results.ConclusionGalangin supresses Beclin-1-dependent autophagy and upregulates the PI3K/AKT signaling pathway to attenuate the neuroinflammatory injury and improve motor coordination ability in PD mice induced by MPTP.